Impact of E-Assessments on the Attitudes and Academic Achievements of Saudi EFL Learners in a Grammar and Vocabulary Test - KADEMI, Abdullahi Salisu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This study investigated the impact of electronic assessments (e-assessments) on the academic achievements of Saudi EFL learners. It also examined their attitudes towards e-assessments and the use of Blackboard for testing. The sample was drawn from the population of preparatory year EFL students at Jubail English Language and Preparatory Year Institute (JELPYI) in Saudi Arabia in 2022–23 academic session. The study adopted a sequential explanatory mixed-methods research design. Quantitative data were collected through a knowledge test and two surveys, while qualitative data were collected via semi-structured interviews. Participants were divided into two groups: the experimental (n = 42), which had access to electronic exercises, worksheets, and assessments via Blackboard, and the control (n = 34), which had access to the same kinds of resources in paper-based formats. It was hypothesised that the experimental group participants would have higher achievements in a post-test and more favourable Blackboard and e-assessment attitudes than those in the control group. After establishing that the two groups were somewhat homogeneous in their academic achievements prior to the treatment, post-test results showed that the experimental group had a statistically significantly higher mean score than the control group, t(74) = 6.235, p =.001. It was also found that the participants had mixed reactions regarding e-assessments and using Blackboard for taking tests, with the experimental group exhibiting more favourable attitudes than the control group. The qualitative findings corroborated the quantitative ones. The study recommended that educational administrators promote technology integration in the classroom due to its immense pedagogical benefits and that teachers incorporate technology to meet the expectations of their digital native students.